Characterisation and fundamental insight into the formation of new solid state, multicomponent systems of propranolol. - Tajber, Lidia (My University, 2021)
The physiochemical properties of acidic or basic active pharmaceutical ingredients (APIs) can be optimised by forming salts with different counterions. The aim of this work was to synthesise a novel salt of propranolol (PRO) using sebacic acid (SEBA) as the counterion and to gain mechanistic understanding of not only the salt formation, but also its eutectic phase formation with SEBA. Thermal analysis showed a solid-state reaction occurring between PRO and SEBA leading to the formation of dipropranolol sebacate (DPS) melting at app. 170 °C and the eutectic composed of DPS and SEBA melting at app. 103 °C, comprising 0.33 mol fraction of PRO as determined by the Tammann plot. X-ray diffraction and Fourier-transform infrared spectroscopy (FTIR) confirmed the identity of the new multicomponent phases of PRO. DPS can be conveniently obtained by heat-induced crystallisation, grinding and conventional solvent crystallisation. Detailed analysis by FTIR revealed H-bond interactions between DPS and SEBA at the inter-phase in the eutectic. Bravais, Friedel, Donnay and Harker crystal morphology coupled with full interaction maps analysis allowed to understand further the nature of interactions which led to formation of the eutectic phase. This work contributes to furthering research on multicomponent pharmaceutical systems to harness their full potential.
PUBLISHED
Keywords: Propranolol; Salt; Eutectic; Mechanochemistry; Thermal analysis; Crystallography; Nanoscience & Materials